Spontaneous Intracranial Hypotension Due to CSF Leak at Multiple Spinal Levels—A Case Report and Literature Review - Saranraj, M.K.; Giridharan, K.; Nathan, Sudhakshina; Babu, Nadasha M.; Balamurugan, Mangaleswaran (Indian Journal of Neurosurgery, 2023)
Spontaneous intracranial hypotension (SIH) is a misdiagnosed condition characterized by low cerebrospinal fluid (CSF) volume and an orthostatic headache that worsens with upright posture due to CSF leak at spinal dural defects. SIH due to CSF leak at multiple spinal levels is a rare condition, and only a few cases have been reported in the literature. Here, we report a case of SIH with a CSF leak at multiple spinal levels. The treatment options and efficacy of epidural blood patch (EBP) injection were discussed in this article.A 36-year-old man presented with complaints of orthostatic headache for 2 months and a computed tomography myelogram demonstrated CSF leaks at multiple spinal levels through the dural defects at C5-C6, C6-C7, C7-T1, T1-T2 levels, and at L1, L2, L3, and L4 vertebral levels on the left side. He was managed with a targeted EBP injection and he improved symptomatically within 24 hours of the EBP injection.SIH is an entity that results from CSF leakage, often through spinal dural defects due to mechanical tear by osteophyte complex, disc prolapse, connective tissue disorders, CSF-venous fistula, and leaking meningeal diverticula. SIH can result from single or multiple dural leaks, but spinal leaks at multiple levels are uncommon. To the best of our knowledge, a total number of 163 cases have been reported in the literature so far. With good success rates, targeted EBP injection with autologous blood is an effective treatment option for both single-level and multiple-level spinal leaks.
Keywords: spontaneous intracranial hypotension; multiple spinal CSF leaks; epidural blood patch injection